2001
DOI: 10.1001/archsurg.136.8.870
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Heller Myotomy and Dor Fundoplication for Achalasia

Abstract: Background: In the treatment of achalasia, surgery has been traditionally reserved for patients with residual dysphagia after pneumatic dilatation. The results of laparoscopic Heller myotomy have proven to be so good, however, that most experts now consider surgery the primary treatment. Hypothesis: The outcome of laparoscopic myotomy and fundoplication for achalasia is dictated by technical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 18 publications
3
65
0
8
Order By: Relevance
“…So it could be argued that the best result of Dor compared to the Nissen is probably not due to the fact that the Nissen lead a major pressure at the LES, instead it is because Dor fundoplication is characterized by a smaller dissection in the hiatal region and provides an anchorage of the margins of the myotomy, and then it keeps them apart during healing, preventing excessive scar shrinkage [11,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So it could be argued that the best result of Dor compared to the Nissen is probably not due to the fact that the Nissen lead a major pressure at the LES, instead it is because Dor fundoplication is characterized by a smaller dissection in the hiatal region and provides an anchorage of the margins of the myotomy, and then it keeps them apart during healing, preventing excessive scar shrinkage [11,32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this was a retrospective study, without a research project, not double-blind and not randomized, meaning it therefore did not need ethical approval [9][10][11].…”
Section: Methodsmentioning
confidence: 99%
“…Ved eksisjon av divertikkelen ble det fripreparert og eksidert, deretter ble m. propria adaptert over eksisjonsstedet. Dessuten ble det i noen pasienter utført Hellers myotomi (9) og Dors fundoplikasjon (9).…”
Section: Diagnostikk Og Behandlingunclassified
“…25) Patti et al reported that impaired visualization of the gastroesophageal junction might be the principal cause of an inadequate cardiomyotomy. 26) Available evidence thus indicates that evaluation of the anterior esophageal fat pad to accurately identify the gastroesophageal junction and a cut length of at least 2 cm in cardiomyotomy are the most important determinants of a successful outcome of Heller myotomy (Fig. 1).…”
Section: Heller Myotomymentioning
confidence: 99%